2020
DOI: 10.3389/fncom.2019.00087
|View full text |Cite
|
Sign up to set email alerts
|

Intra- and Inter-subject Variability in EEG-Based Sensorimotor Brain Computer Interface: A Review

Abstract: Brain computer interfaces (BCI) for the rehabilitation of motor impairments exploit sensorimotor rhythms (SMR) in the electroencephalogram (EEG). However, the neurophysiological processes underpinning the SMR often vary over time and across subjects. Inherent intra-and inter-subject variability causes covariate shift in data distributions that impede the transferability of model parameters amongst sessions/subjects. Transfer learning includes machine learning-based methods to compensate for inter-subject and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
124
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 155 publications
(128 citation statements)
references
References 89 publications
4
124
0
Order By: Relevance
“…Moreover, inter-subject variability, due to anatomical and physiological differences among subjects, also represents an important challenge since it hinders the design of participant-agnostic BCIs. Due to these main challenges (intra- and inter-subject variabilities), most BCIs require time-consuming calibrations to maximize their performance, which makes the creation of one-model-fits-all solutions difficult ( Saha and Baumert, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, inter-subject variability, due to anatomical and physiological differences among subjects, also represents an important challenge since it hinders the design of participant-agnostic BCIs. Due to these main challenges (intra- and inter-subject variabilities), most BCIs require time-consuming calibrations to maximize their performance, which makes the creation of one-model-fits-all solutions difficult ( Saha and Baumert, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the inter-subject template signals are obtained by averaging the partial trials selected from other subjects. Recent studies have demonstrated inter-subject similarity in neural responses occurs because subjects are instructed to perform a specific task over time (Saha and Baumert, 2019 ). Yuan et al presented transfer template-based canonical correlation analysis (tt-CCA) to enhance the detection of SSVEPs by exploiting inter-subject information (Yuan et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recent development of wireless EEG caps and low-cost commercial headsets has substantially reduced the setup time for real-world recordings, however they often come at the cost of precision and reliability. Also, there have been attempts in reducing calibration time by means of machine learning techniques and adaptive classifiers that extract common features among all users (Lotte, 2015 ), known as inter-subject associativity (Saha and Baumert, 2019 ). On the other hand, deep learning methods have been suggested for automatic learning of representations in the brain activity, thereby reducing the pre-processing and manual feature extraction that is required for BCI classifier training (Nagel and Spüler, 2019 ; Tanveer et al, 2019 ).…”
Section: Prospects and Challengesmentioning
confidence: 99%